The effects of using story telling technique in enhancing listening comprehension sub-skills: a case study of year three pupils of SK Lubok Antu, Sri Aman, Sarawak / Doris Raoh - Raoh, Doris (2013)
This study was conducted with the aim of investigating the effectiveness of using storytelling technique in enhancing Year Three Pupils’ listening comprehension sub-skills in Sekolah Kebangsaan Lubok Antu, Sarawak. To answer the questions of the study, the researcher adopted the experimental approach. The sample of the study consisted of 60 Year Three Pupils whereby they were divided into two groups namely the Experimental Group ( 30 pupils ) and Control Group(30 pupils ) .The storytelling technique was used in teaching the experimental group, while the traditional method was used to instruct the control group in the second term of the school year (2013 ). The study examined the improvement shown by the experimental group who received storytelling technique throughout the 6 weeks from the 9th of September to 17th of October. Six stories on local Malaysian Folktales were used to measure the four sub-skills; identifying characters, main ideas, summarizing the stories and predicting. The researcher used pre- and post tests as the main tools of the research. The data of the study were analyzed using T-Test at the significant level of p < 0.05 to identify the effectiveness of using storytelling technique in enhancing SK Lubok Antu Year Three Pupils’ listening comprehension sub-skills namely ; predicting , telling the main idea , recognizing characters and summarizing the events .The study indicated that there is significant difference between the mean scores of the Experimental Group (M =100.0, SD=189.8 ) and the control group ( M= 49.1 , SD=19.9 ) in the Post Test given. Compared with the scores in the Pre -test whereby the Experimental group mean score was ( M= 54.8 SD=17.7 ) and the control group having the scores of ( M=53.3, SD=19.3) . There was an increase in the mean score of both groups however the experimental group had showed tremendous improvement from the mean score of ( M=54.8 ) in the Pre-test to ( M= 100.0 ) in the Post-Test. Thus, it can be said that the Story Telling technique is effective in enhancing the Listening Comprehension sub-skills among the Year Three pupils of Sk. Lubok Antu. Based on the findings, the researcher has recommended using storytelling as a technique to enhance listening comprehension sub-skills .This study has also suggested that further researches should be conducted on the effect of storytelling technique of learning English skills.